Is socio-demographic status, body mass index, and consumption of food away from home associated with high sodium intake among adults in Malaysia?: findings from the Malaysian Community Salt Survey (MyCoSS) - Ruhaya Salleh; Shubash Shander Ganapathy; Norazizah Ibrahim Wong; Siew Man Cheong; Mohamad Hasnan Ahmad; Lalitha Palaniveloo; Fatimah Othman; Azli Baharudin; Megat Rusydi Megat Radzi; Rusidah Selamat; Nur Shahida Abd. Aziz; Rashidah Ambak; et al. (BMC, 2021)
Abstract Background Studies have shown that having away from home meals contributes to high sodium intake among young people and those who lived in urban areas. This study aimed to determine the association between dietary sodium intake, body mass index, and away from home meal consumption behaviour among Malaysian adults. Methods MyCoSS was a cross-sectional household survey involving 1440 adults age 18 years and above. This study utilized stratified cluster sampling to obtain a nationally representative sample. Data was collected between October 2017 and March 2018. Socio-demographic information, dietary assessment using food frequency questionnaire (FFQ), and away from home meal consumption were assessed through a face-to-face interview by trained health personnel. Descriptive analysis and logistic regression were applied to identify the association of socioeconomic status and away from home meal consumption with dietary sodium intake. Results A total of 1032 participants completed the FFQ, with a mean age of 48.8 + 15.6 years. Based on the FFQ, slightly over half of the participants (52.1%) had high sodium intake. Results showed that 43.6% of participants consumed at least one to two away from home meals per day, while 20.8% of them had their three main meals away from home. Participants aged less than 30 years old were the strongest predictor to consume more sodium (adjusted OR: 3.83; 95%CI: 2.23, 6.58) while those of Indian ethnicity had significantly lower sodium intake. Surprisingly, having three away from home meals per day was not associated with high dietary sodium intake, although a significant association (crude OR; 1.67, 95% CI: 1.19, 2.35) was found in the simple logistic regression. Obese participants were less likely to have high dietary sodium intake compared with the normal BMI participants in the final model. Conclusion Over half of the participants consumed sodium more than the recommended daily intake, especially those who consumed three away from home meals. However, there was no significant association between high sodium intake and having three away from home meals per day. The promotion of healthy cooking methods among the public must continue to be emphasized to reduce the dietary sodium intake among Malaysian adults.